2004
DOI: 10.1021/jp0374004
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Route Graphs. I. Theory and Algorithm

Abstract: A theory and algorithm for reaction route (RR) network analysis is developed in analogy with electrical networks and is based on the combined use of RR theory, graph theory, and Kirchhoff's laws. The result is a powerful new approach of "RR graphs" that is useful in not only topological representation of complex reactions and mechanisms but, when combined with techniques of electrical network analysis, is able to provide revealing insights into the mechanism as well as the kinetics of the overall reactions inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 36 publications
2
113
0
Order By: Relevance
“…36 This may be accomplished by appropriately combining the elementary steps into the so-called intermediate reactions (IR). [41][42][43] There are different ways in which the Campbell's DRC, once hence numerically computed for all the steps in a microkinetic model, may be utilized for identification of key steps and model reduction. 46 One such method is the so-called principal component analysis, 40,47,48 in which the eigenvalues and eigenvectors of the matrix X T X are computed.…”
Section: Parametric Sensitivity Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…36 This may be accomplished by appropriately combining the elementary steps into the so-called intermediate reactions (IR). [41][42][43] There are different ways in which the Campbell's DRC, once hence numerically computed for all the steps in a microkinetic model, may be utilized for identification of key steps and model reduction. 46 One such method is the so-called principal component analysis, 40,47,48 in which the eigenvalues and eigenvectors of the matrix X T X are computed.…”
Section: Parametric Sensitivity Analysismentioning
confidence: 99%
“…53 In other words, one needs both thermodynamic (affinity, or reversibility) and kinetic (resistance) characteristics of a reaction step to judge its significance in the overall scheme of things. The electrical network analogy based on the RR graph approach [41][42][43] incorporates both of these aspects. It, thus, comprehensively incorporates and illuminates the network structural constraints embodied by the two Kirchhoff's laws (mass balance, and Hess's law) described below, which further ascribe to reaction networks a complete and quantitative correspondence to electrical networks.…”
Section: Electrical Analogy and Reaction Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Kirchhoff graphs were so-named because they satisfy both the Kirchhoff potential law and the Kirchhoff current law. The use of Kirchhoff graphs as reaction network diagrams was discussed by Fehribach [1], as well as by Fishtik, Datta et al [3][4][5][6], who discuss a related graph, the "reaction route graph". A number of other graphs have been used in the study of reaction networks; a summary can be found in [7,8].…”
Section: Introductionmentioning
confidence: 99%